P4 A 21 year review of transjugular intrahepatic portosystemic shunt placements in university hospital of wales, Cardiff. (28th September 2020) - Arms-Williams, Bradley; Sennitt, Tomos; Wood, Andrew; Raj, Lawrence Sunder; Srivastava, Brijesh; Godkin, Andrew; Gordon, Andrew; Pembroke, Thomas
Abstract : Introduction: Decompensated cirrhosis is associated with poor outcomes and the incidence of advanced liver disease has increased in Wales over the last two decades. Transjugular intrahepatic portosystemic shunts (TIPSS) are an effective treatment of recurrent variceal bleeding and refractory ascites. Methods: A retrospective casenote review of all successful and unsuccessful TIPSS procedures at University Hospital of Wales. Clinical scores were calculated from bloods at the time of TIPSS placement. These cases were then compared to the 2020 BSG TIPSS guidelines 1 for concordance. Results: 93 TIPSS procedures were attempted between March 1999 and June 2020, 85 (91%) of which were successful. The average age was 58 (29–84) and 54 (58%) were male. 72 (77.4%) referrals were from Cardiff and Vale, 19 (20.4%) were from the rest of South Wales, and 2 (2.2%) were from England. The predominant aetiologies of cirrhosis were alcohol (44%), NASH (23%), viral hepatitis (9%) and PBC (6%). The main indications for TIPSS were oesophageal (53%) and gastric (11%) variceal bleeding, resistant ascites (24%), stomal variceal bleeding (6%). Of note, a caecal varix was the indication in one case and GAVE was the indication in two cases (a failed TIPSS that was then repeated successfully in the same patient). The average MELD-Na was 14 (6–29). The average post-TIPSS gradient was 8.5 mmHg (2–13). 30-day survival was 93%. Poorer survival was associated with increasing MELD-Na. All 4 patients with MELD-Na >24 died by day 32. There has been an increase in TIPSS procedures from an average of 1 per year between 1999–2004 to 8 per year between 2017–2019. 11 TIPSS procedures were performed in 2019, all successful. 6 successful TIPSS performed in 2020 so far. Discussion: TIPSS is an effective therapy in selected cases. The demand for TIPSS is increasing. Formalised referral pathways would improve access across South Wales. In alignment with the 2020 BSG TIPSS guidelines 1 a concordant indication was present in 91/93 (97.8%) of cases. Reference: Tripathi, D et al 2020. Transjugular intrahepatic portosystemic stent-shunt (TIPSS) in the management of portal hypertension. Gut 0 :1–20